Twice Punished: Perceived Procedural Fairness and Legitimacy of Monetary Sanctions - Pleggenkuhle, Breanne (Journal of contemporary criminal justice, 2021)
Legal financial obligations (LFOs) are routinely assessed by the courts and corrections agencies. Yet, little is known about how individuals under correctional supervision experience and perceive legal debt. Understanding perceptions of LFOs is critical as research suggests that individuals who believe that criminal justice sanctions are fair and just are more likely to perceive the system as legitimate and comply. The current study examines in-depth interview data with individuals on probation or parole to understand perspectives of LFOs and what factors may condition these views. The results suggest that participants’ views are quite varied—expressing that they deserve some level of financial punishment, particularly in restitution cases, but they question additional costs that are not directly linked to the circumstances of the case, such as supervision fees, that exacerbate a perceived experience of double jeopardy or contradict the perceived purpose of the monetary assessment. Subgroup analyses suggest that individuals with a conviction for a sexual offense have secondary financial sanctions that deepen perceptions of inequities in the system.